Absence of Presence - Binti Zulkifli, Safiah (Cranfield University, 2020)
The tiny the object, the more difficult it is to detect. Failed to detect does not simply signifies the absence of presence. The object may be camouflage and immersed in this huge world - as this image demonstrates! With a booming micro-drones easily available for all walks of life, it is hugely possible for these drones to perform stealthy surveillance being unnoticeable. But, wait! This fact can be avoidable with a specifically design radar for a micro-size target detection. By extracting micro-Doppler signature which is induced by mechanical vibration or rotation from a target – in this case is the flapping wings enable the presence more significant and visible. It is the time to monitor the usage of this presence to avoid illegal and illicit activities for further exploitation. Full control of the latest technology ensure the harmonic and peaceful environment.
Keywords: 'FMCW Radar'; 'DSDS19'; 'DSDS19 Digital Image'; 'Photogrammetry and Remote Sensing'